Strengthening mental health nurses' resilience through a workplace resilience programme: A qualitative inquiry - Foster, Kim; Cuzzillo, Celeste; Furness, Trentham (Journal of psychiatric and mental health nursing, 2018)
Accessible summary What is known on the subject? Mental health nurses are affected by interpersonal, practice‐related and organizational factors that can increase workplace stress and reduce their physical and mental health and well‐being. Resilience programmes are a strength‐based preventative approach to supporting individuals to overcome workplace adversities. What the paper adds to existing knowledge? This qualitative inquiry is the first study to report mental health nurses' perspectives and experiences on a workplace resilience programme. Strengthening mental health nurses' resilience through a resilience programme involved a process of understanding resilience, and applying resilience strategies such as positive self‐talk, managing negative self‐talk, detaching from stressful situations, being aware of and managing emotions, and showing more empathy, to address workplace challenges. To address the range of resources needed to support mental health nurses' resilience, a social–ecological approach to workplace resilience can be used to promote resource provision at individual, work unit, organizational and professional levels. What are the implications for practice? Resilience programmes are one resource for addressing the impacts of workplace stressors on mental health nurses. Organizational barriers and risks to staff well‐being need to also be addressed to build a resilient workforce. Incorporating resilience strategies into clinical supervision or reflective practice models may help sustain beneficial outcomes following a resilience programme and support resilient practice. Introduction Mental health settings are potentially high‐stress workplaces that can lead to nurses' poorer health and well‐being. Resilience programmes are a strengths‐based preventative approach for promoting mental health and well‐being in the face of adversity; however, there is no prior research on mental health nurses' perspectives on resilience programmes. Aim To explore the perspectives of mental health nurses participating in a mental health service‐initiated resilience programme (Promoting Adult Resilience). Method An exploratory qualitative inquiry was undertaken. Multiple qualitative data: open‐ended responses and semi‐structured interviews and focus groups, were thematically analysed. Results Twenty‐nine registered nurses from a metropolitan mental health service participated. Four main themes were as follows: being confronted by adversity; reinforcing understandings of resilience; strengthening resilience; and applying resilience skills at work. Discussion This is the first study to report mental health nurses' perspectives on a resilience programme. Resilience programmes can help improve nurses' self‐efficacy and ability to realistically appraise stressful situations and to moderate their emotional responses to others. Implications for practice It is recommended resilience programmes are provided to promote nurses' well‐being and resilient practices. To build a resilient workforce, the wider barriers and risks to staff well‐being need to be addressed at a unit, organizational and professional level.